PENGARUH KOMBINASI NUTRISI AB MIX DENGAN POC LIMBAH CAIR TAHU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) SECARA HIDROPONIK - Arnis En Yulia; Murniati; Laila Manja (UIR Press, 2022)
This study aims to determine the effect of the combination of AB mix nutrition with POC tofu liquid waste on the growth and yield of lettuce plants and to get the combination of AB mix with POC tofu liquid waste for the best growth and yield of lettuce plants hydroponically. The study was conducted at the Experimental Farm Screening House of the Faculty of Agriculture, Riau University, from September to October 2019. The study used randomized block design (RBD), consisting of a comparison of nutritional treatments, namely: 100% AB mix + 0% POC tofu liquid waste, 75% AB mix + 25% POC tofu liquid waste, 50% AB mix + 50% POC tofu liquid waste, 25% AB mix + 7% POC tofu liquid waste, 100% POC of tofu liquid waste + 0 % AB mix and consisted of 4 replications. The parameters observed were plant height, number of leaves, leaf length, leaf width, root length, fresh weight, root volume, and weight suitable for consumption. Data Anova which showed a significant effect continued with multiple Range Tests at Duncan's 5% level. The results showed that the of nutrition treatment 100% AB mix, combination 50% AB mix + 50% POC tofu liquid waste, and 25% AB mix + 75% POC tofu liquid waste were found similar results, but higher results of giving a combination of 75% AB mix + 25% POC of tofu liquid waste in the leaf number parameter was 11.12 strands, fresh weight was 66.40 g and the proper weight was 58.31 g.